Coastal container multimodal transportation system shipping network design—toll policy joint optimization model. (10th January 2021) - Yang, Zhongzhen; Xin, Xu; Chen, Kang; Yang, Ang
Abstract: A coastal container multimodal transportation system has two modes of transportation, i.e., land and water. Due to economies of scale, the latter has become an emerging way to decrease the pollution of the system. This paper establishes a programming model to improve the system's sustainable transportation policy. The model aims to minimize the carbon dioxide emissions of the system by optimizing two types of policies (i.e., a shipping network design policy and a toll policy) simultaneously. A local optimization algorithm is proposed to solve the abovementioned model. Real-world data on container transportation in the Bohai Rim in Northeast China are used to perform two sensitivity analyses. The running time of each calculation experiment does not exceed 2 minutes, showing the efficiency of the aforementioned algorithm. The experimental results show that the policies can reduce carbon dioxide emissions from container transportation in Bohai Rim from 3.29% to 6.70% under different scenarios. The diminishing marginal utility of the government's sustainable policy is also revealed. Highlights: A model is proposed to optimize coastal transportation sustainability policy. The model can optimize the shipping network design policy and toll policy. Real-world data are used to explore the government's optimal policy scheme.